(untitled) (Research, Society and Development, 2022)
Objective: to analyze the articles that addressed the prevalence of signs and symptoms suggestive of intestinal dysbiosis, in the Brazilian population, which used the metabolic tracking questionnaire (QRM) aimed at dysbiosis as an instrument. Methodology: this is a bibliographic review of the scientific literature in an integrative way, the search for articles was carried out in the following electronic databases: PubMed, Scielo, Web of Science and Academic Google, using as descriptors: Intestinal microbiota, Intestinal dysbiosis and Eating habits. After the search strategy, original studies, developed in Brazil, between 2016 and 2020 were analyzed and selected. Results: 465 articles were found, however, after the screening process, 11 articles were chosen for the preparation of the work. These were cross-sectional studies and all used the QRM, among other strategies to assess the sample. The analyzed studies pointed out several signs and symptoms suggestive of dysbiosis in their populations, but that can be corrected. The most prevalent symptoms of this pathology were: intestinal gas, abdominal discomfort, obesity, cramps, diarrhea and constipation. Conclusion: The knowledge produced demonstrated the importance of using standardized instruments to assess the risk of dysbiosis and indicated that further investigations on the subject are needed.